El vacío y la soledad del no lugar en la obra de Ángeles Marco - Coello, Yolanda Ríos (2016)
The article establishes a relation between the topics, the materials and the elements used in the work of the Valencian artist Angeles Marco with “the non places” of Marc Augé. There are analyzed two of his series “The traffic” and “The jump to the emptiness” looking for the similarities with these not anthropologic places that Augé named “the non places”. Also there is established an analogy of the Valencian artist by the contemporary artist Monika Sosnowska